Prototipe Alat Ukur Densitas BBM Pertalite Berdasarkan SK DIRJEN MIGAS No. 486 Tahun 2017 - Gianto, Gianto (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2025)
The increasing use of pertalite fuel oil (BBM) directly implies a higher risk of fraud. Therefore, it is necessary to conduct quality testing of pertalite fuel, one of which is density testing. In the density testing of fuel at gas stations, the conventional method is generally still used, which involves manually using a hydrometer and thermometer, and then converting it to the standard temperature of 15°C using the ASTM 53B table. This research is designed to develop a prototype of a pertalite fuel density measuring device to accelerate the duration of density testing. This prototype is designed using a 1 kg load cell sensor, a DS18B20 sensor, and a 300 ml measuring cup integrated with an Arduino UNO. Where, using a push button as a tare button and output in the form of 2 LEDs and a 20x4 I2C LCD, using the mass and volume comparison method. The accuracy and precision of the prototype were obtained at 96,88% and 99,41%, with an average testing duration of 41 s to 56 s faster than the conventional method, which averages 125 s. This prototype was calibrated using standard M1 class weights, thermocouples, and a 25 ml pycnometer. The calibration results of the 1 kg load cell sensor showed an accuracy and precision of 99,72% and 99,98%, respectively, while the calibration results of the DS18B20 sensor showed an accuracy and precision of 99,18% and 99,27%, respectively.